PEMBELAJARAN BILANGAN PECAHAN DI SEKOLAH DASAR: Systematic Literatue Review - Sujana, Ghina Zakiyyah (Papanda Publisher, 2022)
In elementary school there are fractions which are one of the mathematics materials taught to students. Fractional numbers are numbers that consist of two parts, namely the number as the numerator and the number as the denominator where the two parts of the number are separated by a slash symbol (/). The format for writing fractions is as follows: where